Elastyczność zatrudnienia w kontekście kształtowania lojalności pracowniczej - Piórkowska-Wojciechowska, Katarzyna (The employment flexibility in the context of employee loyalty creation, 2006)
The main goal of the article is paying attention to the employment flexibility influence on employee loyalty creation. The article presents the concept of employment flexibility, the kinds of employment flexibility and future employment model in the context of employment flexibility. The relations between particular kinds of employment flexibility and employee loyalty are also included
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 265-271